An exploration into experiences and attitudes regarding risky health behaviours in an adult cystic fibrosis population. Issue 8 (13th September 2020) - Keyte, Rebecca; Egan, Helen; Nash, Edward F.; Regan, Anna; Jackson, Craig; Mantzios, Michail
ABSTRACT: Health risk behaviours (HRBs) are prevalent within the cystic fibrosis (CF) population, and there is a lack of research around what influences their engagement. This research explored beliefs associated with HRBs within an adult CF population using qualitative semi-structured interviews. Participants' beliefs towards their CF and its life impact were investigated to explore reasons for engaging in HRB. A desire for normalcy was evident, often accompanied by engagement in everyday HRB as a method of minimising the illness identity. Evidence of a life-orientated illness perspective was also prevalent, with participants engaging in some risky behaviours for fun. Overall, there was a lack of knowledge on the consequences of HRB, with many participants reporting not being informed of these by clinicians. This research highlights a dilemma between clinical recommendations and personal life strategies undertaken by individuals with CF to support their identity.